In vitro and in vivo evaluation in dogs of a miniaturized glucose sensor - Poitout, V.; Moatti, D.; Velho, G.; Reach, G.; Sternberg, R.; Thevenot, D.R.; Bindra, D.S.; Zhang, Y.N.; Wilson, G.S. (ASAIO Transactions, 1991)
A miniaturized glucose sensor was developed, consisting of a platinum wire entirely coated with teflon, except for a 1 mm section near its extremity where glucose oxidase is immobilized. The in vitro sensitivity to glucose of the sensors was 2.3 +/- 0.4 nA/mM, mean +/- SEM (n = 23). These sensors were implanted in the subcutaneous tissue of normal beagles. Two consecutive glucose infusions (15-30 mg/kg/min) were performed. The current generated by the sensor was used for calculation of the sensitivity coefficient (SC) (nA/mM), and the background current in the absence of glucose (lo) (nA). These parameters were used for determination of the apparent subcutaneous glucose concentration. The in vivo sensitivity was less than the in vitro sensitivity (0.5 +/- 0.1 vs. 2.2 +/- 0.2; n = 12 comparisons; p less than 0.01). Stability of sensor function was demonstrated by the absence in variation of SC and lo, calculated from the different plateaus obtained during the glucose infusions. This study provides a simple method for evaluating in vivo the function of a miniaturized sensor implanted in subcutaneous tissue.